Access to Oncology Medicines in Canada: Consensus Forum for Recommendations for Improvement - Sandeep R. Sehdev; Nigel S. B. Rawson; Olexiy I. Aseyev; Catriona J. Buick; Marcus O. Butler; Scott Edwards; Sharlene Gill; Joanna M. Gotfrit; Cyrus C. Hsia; Rosalyn A. Juergens; Mita Manna; Joy S. McCarthy; et al. (Current Oncology, 2024)
Patient access to new oncology drugs in Canada is only possible after navigating multiple sequential systemic checkpoints for national regulatory approval, health technology assessment (HTA) and collective government price negotiation. These steps delay access and prevent health care providers from being able to prescribe optimal therapy. Eighteen Canadian oncology clinicians from the medicine, nursing and pharmacy professions met to develop consensus recommendations for defining reasonable government performance standards around process and timeliness to improve Canadian cancer patients’ access to best care. A modified Delphi methodology was used to identify consensus on 30 questions involving five themes: accountability, disparities, endpoints, timeliness, and cost-effectiveness. It was agreed that greater transparency is required across regulatory and HTA processes. Health professionals in oncology are frustrated for their patients because they are unable to deliver the modern guideline-supported therapies they want to provide due to delays in approval or funding. Canadian health care providers request improvements in timely access to life-saving therapeutics in line with other comparator countries. Clinicians expect urgent improvements in Canadian health systems to give our patients their best chance of survival.